THE PHENOMENON OF VIRTUALITY AND ALGORITHMIC DESIGN - Антоненко, Ігор (SWorldJournal, 2023)
The article provides an expanded understanding of virtual reality and analyzes the processes of development of algorithmic design in Ukraine. The paradigm shift of modern design thinking in the aspect of information technology and the creative process it